The use of “uniform system of accounts for the lodging industry”(usali) in financial reporting in Madeira Archipelago - Murteira, Sara da Luz Benamor (2017)
This Work Project analyses the adoption of the Uniform System of Accounts for the Lodging Industry in the lodging industry in Madeira Archipelago, one of the most important tourism destinations in Portugal. Through a questionnaire directed to 33 financial managers of hotel establishments of various typologies and classifications, this research analyses, amongst others, the USALI’s adoption rate in the region. The findings indicate that USALI’s adoption rate is rather satisfactory - 61% - and that the decision to adopt the USALI was made mainly by owners/shareholders. The main reason reported by non-adopters for rejecting it was the satisfaction with the current accounting system.